Stress and worry in the 2020 coronavirus pandemic: relationships to trust and compliance with preventive measures across 48 countries in the COVIDiSTRESS global survey - Lieberoth, Andreas (2021)
Fil: Lieberoth, Andreas. University Aarhus; Dinamarca.